Innovative business models as drivers for prosumers integration - Enablers and barriers. (July 2021) - Botelho, D.F.; Dias, B.H.; de Oliveira, L.W.; Soares, T.A.; Rezende, I.; Sousa, T.
Abstract: In recent years, traditional power systems have undergone a significant transition, mainly related to the massive penetration of renewable generation. More specifically, the transformation of residential consumers into prosumers has been challenging the existing operation of the electricity market. This transition brings new challenges and opportunities to the power system, leading to new business models. One widely discussed change is related to a consumer-centric or prosumer-driven approach, promoting increased participation of small consumers in power systems. The present paper aims at discussing the recent business models as enablers of the increasing prosumers' role. To do so, it defines the main features of prosumers and their related regulation as well as possible market designs within power systems. In addition, it discusses enabling technologies to properly create the conditions that sustain new prosumer-driven markets. Then, it presents a comprehensive review of existing and innovative business models and a discussion on their future roles in modern power systems. Moreover, a set of recommendations for promoting these business models in the power system is provided. An important conclusion is that, even though economically possible, not all innovative business models can spread around the world due to regulatory obstacles. Highlights: Present a systematic review of business models for prosumers. List of the main regulations and existing business models for prosumers. Discuss the main barriers for a proper integration of prosumers in future power systems. Point to the important technological, markets and regulations aspects. Propose the roadmap for future prosumer business models.